2010
DOI: 10.1111/j.1365-2265.2009.03669.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo‐controlled clinical trial of the effectiveness of thyroxine and triiodothyronine and short‐term exposure to bright light in prevention of decrements in cognitive performance and mood during prolonged Antarctic residence

Abstract: Administration of bright light leads to a significant reduction in serum TSH and prevents increases in anger and depressive symptoms in winter. However, these associations were not observed in summer, suggesting a seasonal influence of photoperiod over temperature upon this intervention in the polar environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Changes in the HPA axis were also detected. Supplements of levothyroxine and exposure to bright light (10,000 lux) during winter had beneficial effects on the observed mood alterations (35,40). During the early adaptation phase (1 mo) of the Concordia winter-over crew in 2008, cortisol levels and stress questionnaires did not report higher stress levels.…”
Section: Antarctica a Testbed For Real Exploration Type Isolation Comentioning
confidence: 88%
See 2 more Smart Citations
“…Changes in the HPA axis were also detected. Supplements of levothyroxine and exposure to bright light (10,000 lux) during winter had beneficial effects on the observed mood alterations (35,40). During the early adaptation phase (1 mo) of the Concordia winter-over crew in 2008, cortisol levels and stress questionnaires did not report higher stress levels.…”
Section: Antarctica a Testbed For Real Exploration Type Isolation Comentioning
confidence: 88%
“…Providing good nutrition and dietary supplements can prevent disease. This could involve previously mentioned levothyroxine (35) or vitamin D (69) supplements. Furthermore, physical exercise was found to be beneficial for a balanced mood in Antarctica (1) and during Mars500 (42).…”
Section: Coping Strategies and Countermeasures In Space Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…The question is not resolved as to whether the overall level of TSH is higher or the rhythm has shifted. However, interestingly when bright light treatment was compared with thyroxine/triiodothyronine supplementation, the bright light was efficient at decreasing TSH, increasing fT3, and prevented anger and depressive symptoms in winter (Palinkas et al, 2010). A change in rhythm is likely to have been evoked by the light treatment and may be the primary explanation for these observations.…”
Section: Polar Studiesmentioning
confidence: 99%
“…Pääkkönen's research suggests that the reason this occurs may have more to do with the darkness of winter than to its cold temperatures. A recently published study by Palinkas and colleagues (6) has shown that thyroid hormones, like melatonin, are also light sensitive and can be influenced by even limited exposure to light therapy during the SPECIAL EDITORIAL winter. Future research in the Antarctic might therefore benefit by examining the role played by darkness, either independently or in combination with, the cold in energy dynamics and its behavioral correlates in the Antarctic.…”
Section: Special Editorialmentioning
confidence: 99%